Rapid cardiovascular aging following allogeneic hematopoietic cell transplantation for hematological malignancy - Dillon, Hayley T.; Foulkes, Stephen; Horne-Okano, Yuki A.; Kliman, David; Dunstan, David W.; Daly, Robin M.; Fraser, Steve F.; Avery, Sharon; Kingwell, Bronwyn A.; La Gerche, Andre; Howden, Erin J. (Frontiers in Cardiovascular Medicine, 2022)
Allogeneic hematopoietic cell transplantation (allo-HCT) offers a potential cure for high-risk hematological malignancy; however, long-term survivors experience increased cardiovascular morbidity and mortality. It is unclear how allo-HCT impacts cardiovascular function in the short-term. Thus, this 3-month prospective study sought to evaluate the short-term cardiovascular impact of allo-HCT in hematological cancer patients, compared to an age-matched non-cancer control group. Before and ~3-months following allo-HCT, 17 hematological cancer patients (45±18years) underwent cardiopulmonary exercise testing to quantify peak oxygen uptake (VO2peak) – a measure of integrative cardiovascular function. Then, to determine the degree to which changes in VO2peak are mediated by cardiac versus non-cardiac factors, participants underwent exercise cardiac MRI (cardiac reserve), resting echocardiography (left-ventricular ejection fraction [LVEF], global longitudinal strain [GLS]), dual-energy x-ray absorptiometry (lean [LM] and fat mass [FM]), blood pressure (BP) assessment, hemoglobin sampling, and arteriovenous oxygen difference (a-vO2diff) estimation via the Fick equation. Twelve controls (43±13years) underwent identical testing at equivalent baseline and 3-month time intervals. Significant group-by-time interactions were observed for absolute VO2peak (p=0.006), weight-indexed VO2peak (p=0.02), LM (p=0.001) and cardiac reserve (p=0.02), which were driven by 26%, 24%, 6%, and 26% reductions in the allo-HCT group (all p≤0.001), respectively, as no significant changes were observed in the age-matched control group. No significant group-by-time interactions were observed for LVEF, GLS, FM, hemoglobin, BP or a-vO2diff, though a-vO2diff declined 12% in allo-HCT (p=0.028). In summary, allo-HCT severely impairs VO2peak, reflecting central and peripheral dysfunction. These results indicate allo-HCT rapidly accelerates cardiovascular aging and reinforces the need for early preventive cardiovascular intervention in this high-risk group.